Three-dimensional Printed Drill Guides Versus Fluoroscopic-guided Freehand Technique for Pedicle Screw Placement: A Systematic Review and Meta-analysis of Radiographic, Operative, and Clinical Outcomes. Issue 8 (October 2020) - Wallace, Nicholas; Butt, Bilal B.; Aleem, Ilyas; Patel, Rakesh
Abstract : Study Design: A systematic review and meta-analysis. Objective: The objective of this study was to compare surgical, clinical, and radiographic outcomes of 3-dimensional printed (3DP) drill guides to the fluoroscopic-guided, freehand placement of pedicle screws in the spine. Summary of Background Data: 3DP is a budding technology in spine surgery and has recently been applied to patient-specific drill guides for pedicle screw placement. Several authors have reported the benefits of these drill guides, but no clear consensus exists on their utility. Materials and Methods: A comprehensive search of the literature was conducted and independent reviewers assessed eligibility for included studies. Outcomes analyzed included: total operation time, estimated blood loss, screw accuracy, pain score, Japanese Orthopedic Association score, and postoperative complications. Weighted mean differences (WMD) and weighted risk differences were calculated using a random-effects model. Results: Six studies with a total of 205 patients were included. There were significantly lower operation times [WMD=−32.32 min, 95% confidence interval (CI)=−53.19 to −11.45] and estimated blood loss (WMD=−51.42 mL, 95% CI=−81.12 to −21.72) in procedures performed with 3DP drill guides as compared with freehand technique. The probability of "excellent" screw placement was significantly higher in 3DP guides versus freehand (weighted risk difference=−0.12, 95% CI=−0.17 to 0.07); however, no differences were observed in "poor" or "good" screw placement. There were no significant differences between groups in pain scores or Japanese Orthopedic Association scores. No difference in the rate of surgical complications was noted between the groups. Conclusions: Pedicle screws placed with 3DP drill guides may result in shorter operative time, less blood loss, and a greater probability of excellent screw placement as compared with those placed with freehand techniques. We conclude that 3DP guides may potentially develop into an efficient and accurate option for pedicle screw placement. However, more prospective, randomized controlled trials are needed to strengthen the confidence of these conclusions. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.